Analisis Kualitas Layanan Website Terhadap Persepsi Pengguna Menggunakan Metode Webqual dan Servqual - Amellia Ayu Permatasari; Mochamad Chandra Saputra; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In the era of information, most of educational institution in Indonesia uses webset as an information media to easiere people to get information from this institution. It is not only for information, website also helps the institution to computerized the manual job. It is can be called as information sistey management. To know the quality of website services, there are two methods, servqual and webqual method which can be used to analized it. From those two methods, which one is to have the most common among the variable in website quality services in the Mathematics department, from the users perception that focus on the quality of website services. The researcher use tservqual method, webqual method, dual regression and factor analysis to measure website services quality. From those methods, regression anlysis shows that the Mathematics department's website is no quite informative. From this research, the researcher hopes that the website services in Mathematics Department can give the service faster and easier to the users.